The Neural Underpinnings of Vicarious Experience - Bernadette M Fitzgibbon (Frontiers Research Topics, 2014)
Everyday we vicariously experience a range of states that we observe in other people: we may "feel" embarrassed when witnessing another making a social faux pas, or we may feel sadness when we see a loved one upset. In some cases this process appears to be implicit. For instance, observing pain in others may activate pain-related neural processes but without generating an overt feeling of pain. In other cases, people report a more literal, conscious sharing of affective or somatic states and this has sometimes been described as representing an extreme form of empathy. By contrast, there appear to be some people who are limited in their ability to vicariously experience the states of others. This may be the case in several psychiatric, neurodevelopmental, and personality disorders where deficits in interpersonal understanding are observed, such as schizophrenia, autism, and psychopathy. In recent decades, neuroscientists have paid significant attention to the understanding of the "social brain," and the way in which neural processes govern our understanding of other people. In this Research Topic, we wish to contribute towards this understanding and ask for the submission of manuscripts focusing broadly on the neural underpinnings of vicarious experience. This may include theoretical discussion, case studies, and empirical investigation using behavioural techniques, electrophysiology, brain stimulation, and neuroimaging in both healthy and clinical populations. Of specific interest will be the neural correlates of individual differences in traits such as empathy, how we distinguish between ourselves and other people, and the sensorimotor resonant mechanisms that may allow us to put ourselves in another's shoes.